Bringing Capital Accumulation Back In: The Weapondollar-Petrodollar Coalition – Military Contractors, Oil Companies and Middle-East "Energy Conflicts" - Jonathan Nitzan; Shimshon Bichler (Review of International Political Economy, 1995)
This paper offers an alternative approach to the repeated occurrence of Middle East “energy conflicts.” Our analysis centres around the process of differential capital accumulation, emphasizing the quest to exceed the “normal rate of return” and to expands one's share in the overall flow of profit. With the evolution of modern capitalism, the dictates of differential accumulation become an ever stronger unifying force, drawing both state managers and corporate executives into increasingly inextricable power driven alliances. The Middle East drama of oil and arms since the 1970s has been greatly affected by this process. On the one hand, rising nationalism and intensified industry competition during the 1950s and 1960s forced the major oil companies toward a greater cooperation with the OPEC countries. The success of this alliance was contingent on the new atmosphere of “scarcity” and oil crisis, which was in turn dependent on the progressive militarization of the Middle East. On the other side of the oil arms equation stood the large U.S. and European based military contractors which, faced with heightened global competition in civilian markets and limited defense contracts at home, increased their reliance on arms exports to oil rich countries. Over the past quarter century, the progressive politicization of the oil business, together with the growing commercialization of arms transfers helped shape an uneasy Weapondollar Petrodollar Coalition between the principal military contractors and petroleum companies. As their environment became intertwined with the broader political realignment of OPEC and the industrial countries, the differential profits of these companies grew evermore dependent on the precarious interaction between rising oil prices and expanding arms exports emanating from successive Middle East “energy conflicts.” At the same time, these companies were not passive bystanders. This is suggested firstly by the very close correlation existing between their arms deliveries to the Middle East and the region's oil revenues and, secondly, by the fact that every single “energy conflict” since the 1967 Arab Israeli War could have been predicted solely by adverse setbacks to the differential profit performance of the large oil companies!
Keywords: 330; arms; exports; accumulation; capital; capitalism; conflict; corporation; crisis; distribution; elite; energy; finance; globalization; growth; imperialism; GPE; liberalism; Middle East; military; national; interest; neoliberalism; new world order; oil; OPE